2019
DOI: 10.1111/jcmm.14667
|View full text |Cite
|
Sign up to set email alerts
|

The role of microvesicles and its active molecules in regulating cellular biology

Abstract: Cell‐derived microvesicles are membrane vesicles produced by the outward budding of the plasma membrane and released by almost all types of cells. These have been considered as another mechanism of intercellular communication, because they carry active molecules, such as proteins, lipids and nucleic acids. Furthermore, these are present in circulating fluids, such as blood and urine, and are closely correlated to the progression of pathophysiological conditions in many diseases. Recent studies have revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 86 publications
3
41
0
1
Order By: Relevance
“…The cargo varies depending on type and differentiation of the parent cell, microenvironmental variables, and agents that triggers EV release. Cargo contents include lipid mediators (e.g., eicosanoids), proteins (e.g., cytokines, chemokines, growth factors or other mediators of signal transduction), genetic material (e.g., mRNAs, long/short noncoding RNAs, nuclear and mt DNA) and, in the case of larger vesicles, whole organelles (e.g., mitochondria) [16][17][18]. While the mechanisms that mediate the biological effects of EVs on their cellular targets remain poorly known, it is clear that EVs are implicated in most, if not all, physiopathological processes, including signal transduction, cell growth, and differentiation, metabolic regulation, embryofetal development, organogenesis, tissue homeostasis and repair/regeneration, antigen presentation and immune response, ageing, pathogen-host interactions, carcinogenesis, tumor invasion/metastasis, cardiovascular dysfunction, etc.…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cargo varies depending on type and differentiation of the parent cell, microenvironmental variables, and agents that triggers EV release. Cargo contents include lipid mediators (e.g., eicosanoids), proteins (e.g., cytokines, chemokines, growth factors or other mediators of signal transduction), genetic material (e.g., mRNAs, long/short noncoding RNAs, nuclear and mt DNA) and, in the case of larger vesicles, whole organelles (e.g., mitochondria) [16][17][18]. While the mechanisms that mediate the biological effects of EVs on their cellular targets remain poorly known, it is clear that EVs are implicated in most, if not all, physiopathological processes, including signal transduction, cell growth, and differentiation, metabolic regulation, embryofetal development, organogenesis, tissue homeostasis and repair/regeneration, antigen presentation and immune response, ageing, pathogen-host interactions, carcinogenesis, tumor invasion/metastasis, cardiovascular dysfunction, etc.…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
“…Additionally, it has been observed that the EV-mediated cargo transfer can occur in an interspecies context [62]. Hence, the EV cargo, which may comprise integrated sets of biological information, is transmitted undiluted and undamaged, and the effects produced can be very strong, even at remarkable distances from the cell of origin [17,18]. Message delivery may be limited to direct activation of PM receptors of the recipient cells or may require internalization via endocytosis or fusion.…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
“…Regarding the protein cargos of microvesicles, they include vesicle-associated membrane protein 3 (VAMP3) that derives from the endosomal recycling pathway, but also MHC class I and II together with the β1 integrin receptor [55,66], supporting a role for microvesicles in the regulation of adaptive immunity. Furthermore, microvesicles can modulate immune responses by transporting cytokines such as IL-1β [67] and nucleic acids such as proinflammatory microRNAs [68].…”
Section: Extracellular Vesicles: Biogenesis and Compositionmentioning
confidence: 99%
“…MVs were directly observed to bud from the plasma membrane in many types of cells, including endothelial cells, platelets, erythrocytes and cancer cells ( 10 ). MVs can carry proteins, lipids and nucleic acids expressed in abovementioned cells to involve in coagulation, immunomodulation, angiogenesis and initiate apoptosis, which is important for the progression of atherosclerosis, coronary heart disease and cancer ( 11 ).…”
Section: Introductionmentioning
confidence: 99%